Canon EOS Rebel T2i/550D digital field guide - Lowrie, Charlotte K. (Digital field guide., 2010)
"Canon's flagship EOS Rebel offers you professional features, ease of use, an advanced HD movie mode, 3.7 frames per second shooting speed, and a lot of fun. This book provides a roadmap to all the settings and controls, but it does a great deal more. It guides you through effective exposure control, super color secrets, tips on using Live View, making the best lens choices, how to take videos, and advice on getting great action, nature, and portrait shots."--Resource description page.